ADOBE INDESIGN 2.0 APPLICATIONS FOR THE MAKING OF AN "OR WRITING WRITING SCIENTIFIC RESEARCH" - Yoseph Wawan Aribowo; Melani Dewi L, SKom, MMSI (Jurnal Sistem Informasi, 2005)
Design and layout of the world is a lonely world behind the scenes during these publications are being looked at by millions of people. Design and layout also involve a lot of details that need accuracy and diligence in managing every element into a single unitary design that was seen and at the same time convey a message effectively.  Lots of media information in a presentation today that unattractive, monotonous and less imaginative, so here the author chose one of the media information that has been a subject of BOOKS in this writing. The book is meant here by the author is "Writing Research or Scientific Writing."  In using Adobe InDesign 2.0, the author will explain how the process to design and arrange the layout of a "Writing or Writing Scientific Research" that can be easily understood the intent and purpose made "Writing or Writing Scientific Research."